2006
DOI: 10.2340/00015555-0065
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dermatologists, Nurses and Pharmacists in Chronic Dermatological Treatment: Patient and Provider Views and Experiences

Abstract: Effectively co-ordinated treatment support from healthcare providers (doctors, nurses and pharmacists) may improve patients' adherence to treatment. The objective of this study was to identify patients' and providers' perceptions of the roles of different healthcare providers in dermatological treatment. Focus groups were used in two types of fora: patients with chronic dermatological diseases (n =2x6) and healthcare providers (n =2x6), including doctors, nurses and pharmacists working in dermatological care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…Unfortunately, making a diagnosis and deciding on treatment is often prioritized during the consultations, leaving limited time for treatment support and attainment of concordance. 19 Furthermore, nonadherence as a potential cause of no response to medication is seldom considered and discussed by physicians. 20 The ideal solution to eliminate problems caused by primary adherence would be to provide medication to the patients directly from the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, making a diagnosis and deciding on treatment is often prioritized during the consultations, leaving limited time for treatment support and attainment of concordance. 19 Furthermore, nonadherence as a potential cause of no response to medication is seldom considered and discussed by physicians. 20 The ideal solution to eliminate problems caused by primary adherence would be to provide medication to the patients directly from the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatology patients have reported that they receive treatment support mainly from the nurses, while physicians are constrained by limited time. 88 Nurses provide hands-on instruction on the application of topical agents and offer individualized feedback. 88 Patients have reported a high level of confidence in their dermatology specialist nurse and valued their accessibility and communication style.…”
Section: Nonphysician Clinicians In Dermatologymentioning
confidence: 99%
“…88 Nurses provide hands-on instruction on the application of topical agents and offer individualized feedback. 88 Patients have reported a high level of confidence in their dermatology specialist nurse and valued their accessibility and communication style. 89 This relationship is an effective component of improving medication adherence.…”
Section: Nonphysician Clinicians In Dermatologymentioning
confidence: 99%
“…Without consideration for the different teaching contexts, it was difficult to identify barriers and enablers to IPW and IPE that may have been specific to each of these contexts or to generalise. For many of the studies, sample demographics, were unspecified, which made it difficult to identify the range of characteristics within the sample groups (Anderson et al, 2009;Anderson & Thorpe, 2010;Baxter & Brumfit, 2008;Gibbon et al, 2002;Lindbland et al, 2006;Reeves & Lewin, 2004;Suter et al, 2009;Wittenberg-Lyles et al, 2010). The studies that were successful in recruiting large samples of staff from a mixture of different mixed professional groups primarily used quantitative methods to collect data (Braithwaite et al, 2012;Chang et al, 2009;Pollard & Miers, 2008;Reid et al, 2006).…”
Section: Strengths and Limitations In Study Samples Sampling Techniqmentioning
confidence: 99%